Pengaruh Rasio Aktivitas, Rasio Profitabilitas dan Rasio Likuiditas Terhadap Nilai Perusahaan Farmasi yang Terdaftar di BEI Tahun 2021-2024 - Risna Nur Ainia; Erghana Kanza Kirana; Hamid Khoirulloh (CV. ITTC INDONESIA, 2025)
Company value is a key factor and attracts investor attention. The capital market plays a crucial role in driving economic growth. Company value reflects the performance, prospects, and level of market confidence in a business entity. Therefore, the higher the company value, the greater investor interest in investing. This study aims to analyze the effect of activity ratios, profitability ratios, and liquidity ratios on company value in the pharmaceutical sector listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. The research method used was quantitative with an associative approach. The sample was determined using a census method, involving all 10 pharmaceutical subsector companies listed on the IDX over a four-year observation period, resulting in 40 observational data sets. The research data came from the companies' annual financial reports obtained from the official IDX website. The results show that the profitability ratio has a significant positive effect on company value, while the activity ratio and liquidity ratio have insignificant effects.